(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Children diagnosed with leukemia often experience significant oral health complications due to immunosuppression and the side effects of chemotherapy. Early detection and systematic monitoring of oral conditions are essential to prevent severe dental and mucosal complications. This study aims to provide a comprehensive assessment of oral health status in children with leukemia and to develop an individualized dental monitoring system to improve preventive and therapeutic outcomes. Clinical examinations, oral hygiene indices, and evaluation of mucosal conditions were conducted in pediatric patients aged 3–15 years undergoing leukemia treatment. The findings indicate a high prevalence of dental caries, gingivitis, mucositis, and xerostomia among these patients. The implementation of an individualized monitoring protocol contributed to improved oral hygiene and early detection of complications. The proposed monitoring system can enhance the quality of dental care and overall well-being of children with leukemia.